2020
DOI: 10.1007/s40489-020-00225-8
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Autism Spectrum Disorder Diagnosis for Young Women and Girls: a Systematic Review

Abstract: There is increased recognition that women and girls with autism spectrum disorders (ASD) are underserved by the clinical criteria and processes required to receive a diagnosis. This mixed-methods systematic review aimed to identify key barriers to obtaining an ASD diagnosis in girls and young women under 21 years. Six themes were identified that focused on perceived gendered symptoms, namely behavioural problems, social and communication abilities, language, relationships, additional diagnoses/difficulties and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
101
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(123 citation statements)
references
References 49 publications
(117 reference statements)
5
101
2
Order By: Relevance
“…Similar results have been obtained by other studies from India (Daley, 2004;Mahapatra et al, 2019;Preeti et al, 2017) and Nepal (Shrestha & Shrestha, 2014). However, there is conflicting evidence on differences in presenting concerns based on sex of the child (Lockwood Estrin et al, 2020), and we found some indication of lack of language being a presenting concern more often for girls than boys. This might relate to the theme that emerged from in-depth interviews that there is a widespread belief that boys speak later than girls.…”
Section: Discussionsupporting
confidence: 92%
“…Similar results have been obtained by other studies from India (Daley, 2004;Mahapatra et al, 2019;Preeti et al, 2017) and Nepal (Shrestha & Shrestha, 2014). However, there is conflicting evidence on differences in presenting concerns based on sex of the child (Lockwood Estrin et al, 2020), and we found some indication of lack of language being a presenting concern more often for girls than boys. This might relate to the theme that emerged from in-depth interviews that there is a widespread belief that boys speak later than girls.…”
Section: Discussionsupporting
confidence: 92%
“…Some parents may have attributed their child's differences or delays to the common perception that male children develop social communication skills more slowly than females. A complementary interpretation could be that parents of females were relieved that the telehealth procedures were sensitive enough to identify autism in their daughters considering previously documented barriers to diagnosis among females (Estrin et al, 2020). Without comparison data from traditional diagnostic models, it is difficult to determine whether parents of males find the telehealth model less acceptable or if they were less satisfied with the general diagnostic process.…”
Section: Discussionmentioning
confidence: 99%
“…Is it worth mentioning the study conducted by Lockwood-Estrin and collaborators [ 74 ] in which they carried out a systematic study to determine the possible intrinsic difficulties that could be the basis for the existing biases in women’s ASD diagnosis (i.e., in girls and young women under 21 years of age). They identified two main groups of possible difficulties.…”
Section: Other Theoretical Approachesmentioning
confidence: 99%